PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI ( STUDI KASUS PADA PENUMPANG KERETA API KELAS EKSEKUTIF ARGO SINDORO PT. KAI DAOP IV SEMARANG ) - Nabil Musyaffa; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2019)
People nowadays always looking out for the fast, efficient and comfortable transportation to travel from one place to other. One of the transportation that matched with the criteria already being mentioned is railway transportation and PT. Kereta Api (Persero) is a state-owned facilities and infrastructure that manages the railway transportation in Indonesia. To compete against the other transportation company, PT Kereta Api Indonesia especially in DAOP IV Semarang has already offered an executive class train for the passenger who wants to feel the comfort, and the product name is Argo Sindoro. The argo sindoro is an effort from PT KAI DAOP IV Semarang to boost customer satisfaction and customer loyalty. The aims of this study is to identify the effects of price and service quality to customer loyalty through customer satisfaction. The type of this research is explanatory research. Sampling techniques using purposive and accidental sampling. Population of this research is the passengers of Argo Sindoro train. The data was analyzed using SPSS 21.0 for Windows.